PWE-068 Correlation of a patient reported single item global disease rating scale to clinical and biological markers of disease activity. (22nd June 2015) - Rimmer, M; Asher, R; Jackson, R; Race, G; Collins, P; Dibb, M; Probert, C; Rhodes, J; Subramanian, S
Abstract : Introduction: Multiple instruments exist to assess disease activity in inflammatory bowel disease (IBD). However, several factors preclude routine clinical use of these instruments. These include time limitations, need for separate tools in Crohn's disease (CD) and ulcerative colitis (UC) and finally the inability to fully capture the burden of disease from a patient's perspective. A simple easy to use patient reported outcome measure will help inform clinical decision making. We evaluated the correlation of a single item patient reported disease control scale to physician assessment, clinical and biological markers of disease activity. Method: We conducted a single centre prospective cross-sectional study. Patients with IBD (with the exception of ostomy patients) attending clinic at the Royal Liverpool University Hospital were eligible for inclusion. Disease activity was assessed using Harvey-Bradshaw Index (HBI) for CD or simple clinical colitis activity index (SCCAI) for UC. Patients were asked to rate the control of CD or UC on a numerical scale verbally in response to 'How do you rate the control of your CD or UC today on a scale of 0–10, 10 being the best?'. Information on blood tests including C-reactive protein (CRP) was collected if these were requested as part of routine clinical care. The study was approved by Liverpool Research Ethics Committee as part of an on-going prospective IBD registry study. Results: A total of 176 observations, median age 38.5 (IQR 25–53) were included. 98 patients (56%) had CD and 72 had UC (44%). Both HBI and SCCAI showed a significant association with the single item patient-reported score (Kruskall-Wallis, p < 0.001). Across all patients a score of at least 8 (IQR 8–10) corresponded to remission on HBI and SCCAI (Table 1 ). The degree of agreement between patient scoring and activity index was substantially better for UC/SCCAI (kappa score 0.65) than for CD/HBI (kappa 0.39), possibly reflecting the emphasis of CD activity scores (HBI and CDAI) on diarrhoea rather than other symptoms such as fatigue. There was no significant association between CRP and patient reported global rating scale for both CD and UC (p = 0.7). Conclusion: A simple "instant" patient reported score for disease control can be readily obtained in the clinic and shows good correlation with more complex scores. In Crohn's disease, particularly, it might give a fairer reflection of the patient's wellbeing than conventional more complex scores. Disclosure of interest: None Declared.